2002
DOI: 10.1037/0735-7036.116.4.342
|View full text |Cite
|
Sign up to set email alerts
|

Responses to olfactory stimuli in spotted hyenas (Crocuta crocuts): II. Discrimination of conspecific scent.

Abstract: Scent marking in spotted hyenas (Crocuta crocuta) includes the deposition of anal sac secretions, or "paste," and presumably advertises territorial ownership. To test whether captive hyenas classify and discriminate individuals using odor cues in paste, the authors conducted behavioral discrimination bioassays and recorded hyena investigation of paste extracted from various conspecific donors. In Experiment 1, subjects directed most investigative behavior toward scents from unfamiliar hyenas and members of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…A prior study of a captive colony of spotted hyenas showed that they discriminated readily between the pastes of males and females in the colony, indicating that paste odor profiles, on a local scale, were sex specific (25). A different, population-level study of spotted hyenas in the Serengeti National Park, Tanzania, did not find evidence that sex affected paste odor profiles (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior study of a captive colony of spotted hyenas showed that they discriminated readily between the pastes of males and females in the colony, indicating that paste odor profiles, on a local scale, were sex specific (25). A different, population-level study of spotted hyenas in the Serengeti National Park, Tanzania, did not find evidence that sex affected paste odor profiles (24).…”
Section: Discussionmentioning
confidence: 99%
“…The major volatile constituents in paste are volatile fatty acids (VFAs), esters, hydrocarbons, alcohols, and aldehydes (23,24). Previous investigations have shown that the odors of spotted hyena pastes vary with individual identity, group membership, sex, and, potentially, female reproductive state (16,24,25). Effects of striped hyena traits on paste odors have not yet been investigated.…”
mentioning
confidence: 99%
“…Individual scent signatures have been shown, either chemically or behaviourally, to characterize a wide range of social species (bats [46]; voles [47]; spotted hyaenas [48]; lemurs [22,24]; humans [49]), suggesting that communication of identity is critical for maintaining social relationships, even between members of individualized societies. In lemurs, contraception altered otherwise stable patterns in female scent signatures (effectively changing their normal chemical identity) and decreased the chemical distance between females (effectively degrading the individual distinctiveness of their odours).…”
Section: Discussionmentioning
confidence: 99%
“…Male hyenas frequently sniff female conspecifics, presumably to evaluate each female's reproductive state via pheromonal cues (Drea et al, 2002b). It is, therefore, interesting that time to conception emerged here as the only significant female characteristic influencing a male hyena's decision to stay with a female after he has sniffed her ( Table 2).…”
Section: Male Reproductive Tacticsmentioning
confidence: 97%